2018
DOI: 10.1016/j.cma.2018.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Skew-symmetric Nitsche’s formulation in isogeometric analysis: Dirichlet and symmetry conditions, patch coupling and frictionless contact

Abstract: A simple skew-symmetric Nitsche's formulation is introduced into the framework of isogeometric analysis (IGA) to deal with various problems in small strain elasticity: essential boundary conditions, symmetry conditions for Kirchhoff plates, patch coupling in statics and in modal analysis as well as Signorini contact conditions. For linear boundary or interface conditions, the skew-symmetric formulation is parameter-free.For contact conditions, it remains stable and accurate for a wide range of the stabilizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 89 publications
0
20
0
Order By: Relevance
“…Here the objective is to force the temperature continuity in a stricter sense and normal flux continuity in a weaker sense. In the literature [30,31], it is also reported that the large stabilization parameter might cause ill-conditioning of the system, but we did not face any conditioning issue for our boundary value problem. For the averaging parameter, a standard value γ = 0.5 is taken, which gives equal weights to fluxes on both sides of the interface.…”
Section: Boundary Value Problemmentioning
confidence: 88%
See 1 more Smart Citation
“…Here the objective is to force the temperature continuity in a stricter sense and normal flux continuity in a weaker sense. In the literature [30,31], it is also reported that the large stabilization parameter might cause ill-conditioning of the system, but we did not face any conditioning issue for our boundary value problem. For the averaging parameter, a standard value γ = 0.5 is taken, which gives equal weights to fluxes on both sides of the interface.…”
Section: Boundary Value Problemmentioning
confidence: 88%
“…In addition to that, it keeps the coercivity of the bilinear form intact and the variational form consistent. Nitsche's method has been successfully applied for patch coupling in [30,31]. When Nitsche's method is applied to couple patches, the linear form (Equation ( 6)) on the right side remains the same, while the bilinear form (Equation ( 5)) is altered as follows, (8) where n is the normal at Γ I for any one patch from the patches connected at Γ I (n = n 1 = − n 2 ), β is the stabilization parameter.…”
Section: Boundary Value Problemmentioning
confidence: 99%
“…These difficulties are: (i) the performance of local refinement [11], (ii) an automatic parameterisation to build the approximation, (iii) enforcement of multi-patch constraints, and (iv) the need for an interior parameterisation to be constructed from the CAD data, which only provides boundary information [12]. Several methods were later devised in order to alleviate the difficulties faced by IGA [13][14][15]. And more details about IGA can be found in review papers [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The Kirchhoff-Love type elements are rotation-free and are only valid for thin structures. Due to the absence of rotational degrees of freedom (DoFs), special techniques are required to deal with the rotational boundary conditions [9,15,16] and multi-patch connection [17]. Theoretically, the Reissner-Mindlin theory is valid for both thick and thin structures, however it is observed from the literature [11,18] that both the FEM and the IGA approaches suffer from locking for thin structures when the kinematics is represented by Reissner-Mindlin theory, especially for lower order elements and coarse meshes.…”
Section: Introductionmentioning
confidence: 99%